PTU-081 Use of the enhanced liverpool liver abdominal ratio (elaar) to predict outcome in patients assessed for transjugular intrahepatic porto-systemic shunt (tips). (17th June 2017) - Swaminathan, M; Smith, L; Kibriya, N; Kumar, P; Cross, T
Abstract : Introduction: TIPS is an effective treatment for patients with refractory variceal bleeding and diuretic resistant ascites. Patient selection is a vital component to the success of TIPs. Liver volume may be a determinant in TIPs outcome, as it may indicate liver reserve. A previous study using the liver to abdominal area ratio (LAAR), has been shown and validated to be effective at determining prognosis in patients with end stage liver disease. The utility of this tool in the setting of TIPs has not been previously evaluated. Aims: To assess the use of (eLAAR) in determining outcome following TIPS. Method: Retrospective-prospective study of TIPs patients in Liverpool, UK (Aintree University Hospital, Royal Liverpool Hospital) January 2010 to September 2016. Only patients undergoing TIPS were included. Parameters collected included: gender, disease aetiology, albumin, bilirubin, platelets, prothrombin time, creatinine, sodium, and TIPs indication. Liver and abdominal areas were measured from cross-sectional imaging taken no more than three months prior to the procedure. Measurements will be taken by radiologists or clinicians trained in the measurement technique required. The primary outcome measure was death from date of TIPs. Results: 179 patients were identified, after exclusions 115 patients were in the final analysis. 86 (75%) were male. The indications for TIPs were: 108 variceal bleeding and 7 diuretic resistant ascites. The disease aetiology was ALD 77 (67%), NASH 14 (12.2%), hepatitis C 4 (3.5%), Autoimmune 2 (1.7%), mixed alcohol 12 (10.4%) and others 6 (5.2%). The median MELD score was 22.2 (IQR 20.8–24.4), and eLAAR score was 45.2 (IQR 38.1–50.55). Survival at 90 days, 1 and 2 years, and overrall post TIPs was 80.9%, 77.4%, 70.4% and 59% respectively. The median eLAAR between survivors and non survivors were 42.4 and 47.3. Bilirubin was significant in predicting death at 90 days, 1 year and 2 years (p=<0.001), MELD was significant at 90 days and 1 year (p=0.007, p=0.006). eLAAR predicted overall survival, p=0.008. On logistic regression analysis, bilirubin and eLAAR were significant in predicting overall mortality (p=0.003 and p=0.02 respectively). The optimal cut-off for eLAAR to predict death was 45.1 (p=0.02, OR 2.5). Conclusion: Early death post TIPs was best predicted using MELD or bilirubin. Overall survival was best predicted with eLAAR and bilirubin. The higher eLAAR score than anticipated from previous studies may be a reflection of a higher proportion of alcoholic hepatitis patients. The use of eLAAR in severe liver disease warrants further study. Disclosure of Interest: None Declared